Customary Law and Social Capital Synergy for Paya Nie Peatland Governance - Sela Azkia; Fitri Maghfirah; Faisal Faisal; Muammar Muammar; Nazwa Salsabila; Cristian Hans Pebrianta Sitepus (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Peatland ecosystems such as Paya Nie hold strategic ecological and socio-economic value as carbon sinks, biodiversity habitats, and community livelihood sources. Specific background: Despite these roles, Paya Nie faces degradation due to land conversion and weak enforcement of conservation norms. Customary law historically guided sustainable use, but its oral nature and reliance on social sanctions reduce its effectiveness in the face of modernization. Knowledge gap: Previous studies have emphasized either the ecological or legal dimensions but have rarely examined the synergy of customary law, social capital, and national law in peatland governance. Aims: This study employs a normative juridical method enriched with a socio-legal perspective to analyze the position of customary law in Indonesia’s legal system and its integration with social capital for ecological sustainability. Results: Findings confirm that while customary law is constitutionally recognized, its enforcement is limited, requiring revitalization through codification, strengthened social capital, and harmonization with national regulations. Novelty: The study introduces a governance model that integrates customary law, social capital, and state law as a synergistic framework for sustainable peatland management. Implications: This model contributes theoretically to socio-legal discourse and practically to policymaking, offering adaptive, participatory, and sustainable solutions for environmental conservation and community empowerment. Highlights: Integration of customary law, social capital, and national law strengthens peatland management. Codification and formal recognition enhance the enforcement of customary norms. Synergy model offers adaptive and participatory governance for sustainability. Keywords: Customary Law, Social Capital, Peatland Conservation, Environmental Governance, Sustainability